Zapisy i fundacje rodzin krakowskich na rzecz opieki nad dziećmi i dorosłymi w drugiej połowie XIX wieku - Ślęczka, Ryszard (Karkonoska Państwowa Szkoła Wyższa, 2011)
In the second half of the 19 century in the Polish territory appearred a numerous of foundations and institutions for children and adults welfare. It is worth to mention operation of August Jozef Iliński in Rowne (Wołyń) and clergyman Jakub Falkowski, which in 1917 contributed to the establisment of Institute for Deaf People in Warsaw. Since 1917 in Cracow was functioning Benevolent Society which was managing numerous endowments received by Cracow hospitals. The Society was running an extensive charitable activity, a school, shelters for the orphans and old people. It organized also purchase of food, clothing, combustible and medicins for the poor. Siemaszko's Institution for Boys in Długa Street and Prądnicka Street owns its existence to generosity of the benefactors. A4-class-school, workshops and accomodation for 400 boys were run by this institution. It is worth to mention St. Joseph'sInstitution for the orphaned boys, which existed owing to Piotr Michałowski's endowment, and the initiatives of Henryk Jordan having aimed to an establisment of Society for Catholic Workers' Cheap Accomodation as well as Jordan's public garden eagerly visited by Cracow dwellers until now. Among the most significant individual endowments of the most remarkable is a 2 million franc legacy of Aleksander Lubomirski for an establisment of an educational institution for the neglected boys in Rakowiecka Street, and House of the Poor initiated owing to benevolence of Anna and Ludwik Helcel.
Keywords: fundations; care; education; hospitals; care institutions; children; adults